Fungus Infections After Liver Transplantation - Schröter, Gerhard P. J. (1977)
The problem of fungus infections after liver transplantation was studied. In 100 consecutive recipients of orthotopic liver homografts there were 10 and 8 examples, respectively, of localized and disseminated infections caused by Candida species. Candidemia was demonstrated in 8 of these 18 patients. One patient who had a localized Candida infection also had disseminated cryptococcosis. An additional 31 patients were infested in that Candida could be cultured from sites where it is not normally found, such as the blood (8 examples), urine (8), ascitic fluid (8), and wounds (22). This exorbitant incidence of monilial infections and infestations was associated with a high frequency of complications involving the homograft as well as the hosts' gastrointestinal tract during the post-transplantation period. The yeasts found in blood, urine, ascitic fluid and elsewhere were thought to have originated from the gut. Ten of the 100 patients had aspergillosis which was localized in 7 instances and disseminated in 3. The lung was the most frequently affected organ. The fungus infections played a contributory role in the downhill course of our patients but in the event of death more fundamental and more frequent causes of failure were technical complications involving the homografts, difficulties in controlling rejection with reasonable immunosuppressive doses and bacterial sepsis. Suggestions have been made for the better control of fungal infections in liver recipients.